2019
DOI: 10.3329/bjp.v14i4.42414
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic phenolic constituents from the leaves of Ehretia asperula

Abstract: Cytotoxic phenolic constituents from the leaves of Ehretia asperula Sir, The genus Ehretia is mainly distributes in tropical areas of Asia, Africa, Northern America and exhibited valuable pharmacologial properties (Li et al., 2010; Shukla and Kaur, 2018). In Vietnam, Ehretia asperula Zoll. & Mort. has been used in traditional medicine for the treatment of ulcer, tumors, liver disease and inflammation (Nguyen et al., 2017). To date, there are few reports about the biological activities and chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Most likely, the E. asperula is a perennial woody plant and the polyphenol accumulation might not yet enter the main stage, so the influence of AM fungus at this experimental time was not significant. Normally, after two-year growth, the bioactive substances accumulating in E. asperula biomasses are enough to harvest and use (Nguyet et al, 2018;Kim et al, 2019). Maybe, it is still early to see an obvious effect of the AM fungus on the polyphenol production in E. asperula plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, the E. asperula is a perennial woody plant and the polyphenol accumulation might not yet enter the main stage, so the influence of AM fungus at this experimental time was not significant. Normally, after two-year growth, the bioactive substances accumulating in E. asperula biomasses are enough to harvest and use (Nguyet et al, 2018;Kim et al, 2019). Maybe, it is still early to see an obvious effect of the AM fungus on the polyphenol production in E. asperula plants.…”
Section: Discussionmentioning
confidence: 99%
“…E. asperula is a perennial woody plant and S. procumbens is an herb. The source of medicinal substances obtained from these species has been studied and proven to have anticancer and anti-inflammatory properties (Nguyen et al, 2017;Nguyet et al, 2018;Kim et al, 2019;Tran et al, 2019). However, studies on the effects of microflora in general or AM fungi in particular on the growth and production of medicinal substances of these two species are very few.…”
mentioning
confidence: 99%
“…Some researchers have recently revealed the potential pharmacological effects of E asperula in cancer treatment 13 , but there are no trial results using E asperula in cancer therapy. One study identified that the leaves of E asperula contained several constituents with anti-cancer properties, but the underlying mechanisms responsible for these effects are unknown 14 . Only a few reports to date have characterized the chemical components of this plant and their biological effects, particularly on eye disease.…”
Section: Introductionmentioning
confidence: 99%